277 Body mass index at time of diagnosis is predictive of future disease activity in SLE. (April 2019) - Stojan, George; Magder, Laurence; Goldman, Daniel; Petri, Michelle
Abstract : Background: Obesity is more common in patients with SLE compared to the general population. The prevalence of obesity among SLE patients is between 28 and 50 percent. We previously demonstrated an inverse correlation between body mass index and disease activity in systemic lupus, even after adjusting for prednisone dose. The question of whether these findings were epiphenomena related to disease activity itself remained unanswered. We thus hypothesized that the BMI at cohort entry was predictive of future disease activity. Methods: 2406 patients in a prospective SLE cohort had their weight assessed at cohort entry. Patients were categorized into five predetermined groups based on weight: low (BMI <20 kg/m2), normal weight (reference, BMI 20–24.9 kg/m2), overweight (25–29.9 kg/m2), obese (BMI 30–34.9 kg/m2), and severely obese (BMI >35 kg/m2). Disease activity was characterized on the basis of SLE Disease Activity Index (SLEDAI) scores; for each BMI category we created an Adjusted Mean SLEDAI score. This involved calculating the area under the curve of SLEDAI scores over time. The area under the curve between each two visits was the average of the SLEDAI values at those two visits multiplied by the length of time between the two visits. All the calculated areas were then summed and divided by the total length of the time period. The adjusted mean SLEDAI had the same units as SLEDAI. The adjusted mean SLEDAI has been shown to be a valid measure of SLE activity. To calculate adjusted mean of SLEDAI over time, we only included patients attending the clinic at 3 month intervals for a minimum of 3 visits. 1896 patients were included in the analysis. 1763 (93.0%) were females. Majority (53.0%) were Caucasians, 39.0% African American. To determine whether BMI at cohort entry was predictive of future disease activity, we compared the categorized BMI at cohort entry with the adjusted mean SLEDAI by pairwise t test and ANOVA test. Results: See table 1 . Conclusions: Body weight at cohort entry was predictive of future disease activity. Overweight and obese patients had a significantly lower adjusted mean SLEDAI over time (p<0.05). This analysis adds further support to the existence of an obesity paradox in SLE. Funding Source(s): The Hopkins Lupus Cohort was funded by AR 69572